The Importance of Midwifery Services in Achieving Healthy Cities: A Review Article - Fatmazehra AKPINAR SELVASLI; Serap EJDER APAY (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: WHO has developed the Healthy Cities Project, based on how a city can be a healthy city. Effective delivery of midwifery services is very important in delivering healthy services to all segments of the society. In this study, we aimed to draw attention to the importance of effective provision of midwifery services in the way of being a healthy city. Methods: Data were collected using the literature review method. The keywords